Journalist Intimidation as an Information Control Strategy: A Systematic Literature Review of Violence Against Independent Media in Indonesia - Ayunda Ganesha Gita; Riani Rahma Vita Sari (Global Writing Academica Researching & Publishing, 2026)
Press freedom, as a pillar of democracy, continues to face serious threats through practices of intimidation against journalists, both physical and digital. This study uses the Systematic Literature Review (SLR) method to examine academic literature and reports from international institutions for the period 2021–2025 regarding the forms of threats, impacts, and strategies for protecting journalists. The study results show that intimidation occurs in the form of physical threats, symbolic terror, and digital attacks such as doxing, sexual harassment, online mobs, and hacking. These threats result in psychological trauma, self-censorship, and a decline in the quality of investigative reporting, thus eroding press freedom and, consequently, democracy. Collective coping strategies in newsrooms have proven helpful, while technological innovations based on automated detection offer preventative measures, although they still require transparency and strong regulations. In the Indonesian context, journalists face a combination of physical, digital, and symbolic threats, highlighting the high vulnerability of independent media. Thus, multidimensional protection through strong legal regulations, collective solidarity, and technological support is needed to enable the press to fulfill its function as a pillar of democracy.